A Critical Study on the Juridical Position of Intention in Prayer: An Analysis Within the Framework of Fiqh Al-Hadith - Muzakkir (El-Sunan: Journal of Hadith and Religious Studies, 2025)
The study of intention (niyyah) in prayer constitutes one of the pivotal discourses in Islamic law that has been continuously debated throughout the history of scholarly thought. Intention, as the essence of every act of worship, not only determines the validity of the act but also serves as a measure of its spiritual value before Allah (SWT). Divergent perspectives emerge when scholars situate intention within the framework of ritual jurisprudence, particularly regarding whether it constitutes a pillar (rukn) or merely a condition (sharṭ) of prayer. The Shāfiʿī school maintains that intention is a pillar of prayer, viewing it as an intrinsic component of worship itself, whereas the Ḥanafī, Mālikī, and Ḥanbalī schools classify it as a condition for the validity of prayer, arguing that intention accompanies prayer externally, similar to the role of purification (ṭahārah). This divergence in classification is rooted in the diversity of juristic methodologies (istinbāṭ) and principles of legal theory (uṣūl al-fiqh) employed in interpreting scriptural sources, particularly the well-known prophetic tradition, “innamā al-aʿmāl bi al-niyyāt” (“actions are only judged by intentions”). This research adopts a qualitative method with a library-based approach, drawing on both classical and contemporary literature in the fields of uṣūl al-fiqh and hadith. The analysis employs a descriptive-analytical method, first outlining scholarly opinions and subsequently subjecting them to critical examination in order to ascertain the position of intention within the structure of prayer. The findings indicate that, despite differences in juristic classification, all schools unanimously agree that intention is an indispensable element of prayer. The distinction between its classification as a pillar or a condition is not contradictory; rather, it reflects the breadth of Islamic legal methodology, which ultimately enriches the intellectual tradition of fiqh. Consequently, intention retains its central role as the determinant of both the validity and the spiritual merit of worship, underscoring the importance of integrating both the outward and inward dimensions in the performance of prayer.